ANALYSIS OF ASSERTIVE SPEECH ACTS IN MINISTER NADIEM MAKARIM'S FINAL SPEECH ON NATIONAL EDUCATION DAY - Rambe, Aisyah Arfani; April Yanti; Desi Ramadali Hutauruk (ELP (Journal of English Language Pedagogy), 2025)
This article analyzes assertive speech acts in Nadiem Makarim's last speech  as Minister of Education, Culture, Research, and Technolog on education national day Using a pragmatic approach, this study identifies the types of assertive speech acts used and their functions in conveying messages to the audience. This study aims to to identify the types of assertive speech acts used and their communicative functions in the context of the speech and also to explore the use of assertive speech acts in Nadiem Makarim's speech to understand their communicative functions and effectiveness in a formal context. Using a descriptive qualitative approach, cpthis study examines the speech transcript to classify assertive speech acts based on their type and function, drawing on frameworks from pragmatics.". The results of the study show that the analysis revealed the frequent use of assertive acts such as stating to build credibility, suggesting to inspire action, and reminding to emphasize shared goals These insights contribute to understanding effective public communication strategies and enhance the study of speech acts in formal and political contexts.